2013
DOI: 10.1371/journal.pone.0058122
|View full text |Cite
|
Sign up to set email alerts
|

Human Herpesvirus 6A Partially Suppresses Functional Properties of DC without Viral Replication

Abstract: Human herpesvirus 6A (HHV-6A) is a common virus with a worldwide distribution that has been associated with multiple sclerosis. Whether HHV-6A can replicate in dendritic cells (DC) and how the infection might modulate the functional properties of the cell are currently not well known and need further investigations. Here, we show that a non-productive infection of HHV-6A in DC leads to the up-regulation of HLA-ABC, via autocrine IFN-α signaling, as well as the up-regulation of HLA-DR and CD86. However, HHV-6A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 36 publications
5
20
0
Order By: Relevance
“…Whereas, Hirata et al ( 2001 ) suggests that DC can support HHV-6A (U1102 strain) replication by increase in protein load over time, Smith et al ( 2005 ) suggests that DC cannot support HHV-6A (GS strain) replication as no increase in intracellular viral DNA was seen over time. We did not detect any increase in either viral protein or DNA when infecting DC with HHV-6A (GS strain) (Gustafsson et al, 2013b ), thus supporting the report by Smith et al To control for degraded virus or suboptimal infections both Smith et al and we infected susceptible cells in parallel with DC using the same virus supernatants. Productive infection was seen in the susceptible cells suggesting that lack of viral replication seen in DC was not due to problems with the virus stock or infection procedure.…”
Section: Virus Replicationsupporting
confidence: 87%
See 1 more Smart Citation
“…Whereas, Hirata et al ( 2001 ) suggests that DC can support HHV-6A (U1102 strain) replication by increase in protein load over time, Smith et al ( 2005 ) suggests that DC cannot support HHV-6A (GS strain) replication as no increase in intracellular viral DNA was seen over time. We did not detect any increase in either viral protein or DNA when infecting DC with HHV-6A (GS strain) (Gustafsson et al, 2013b ), thus supporting the report by Smith et al To control for degraded virus or suboptimal infections both Smith et al and we infected susceptible cells in parallel with DC using the same virus supernatants. Productive infection was seen in the susceptible cells suggesting that lack of viral replication seen in DC was not due to problems with the virus stock or infection procedure.…”
Section: Virus Replicationsupporting
confidence: 87%
“…The vast majority of studies investigating HHV-6A or 6B infection in DC have studied MDC. The literature provides contradictory reports on the replication capacity of HHV-6A (Hirata et al, 2001 ; Smith et al, 2005 ; Gustafsson et al, 2013b ) (Table 1 ). Whereas, Hirata et al ( 2001 ) suggests that DC can support HHV-6A (U1102 strain) replication by increase in protein load over time, Smith et al ( 2005 ) suggests that DC cannot support HHV-6A (GS strain) replication as no increase in intracellular viral DNA was seen over time.…”
Section: Virus Replicationmentioning
confidence: 99%
“…Our work emphasizes, in fact, that HHV-6 infection induces a high frequency of virus-specific Tregs compared to HCMV-specific T-cell responses. These Tregs can have a broad immunosuppressive capacity and inhibit innate and adaptive immune-cell functions, which may be crucial for HHV-6-mediated latency and survival (24,25,36). In line with this possibility, we found that the frequency of HHV-6-specific regulatory T cells was inversely correlated with the frequency of conventional effector/memory T cells.…”
Section: Discussionsupporting
confidence: 73%
“…Like other beta-herpesviruses, HHV-6B can trigger immuneevasion mechanisms (reviewed in [49, [50]]). Among the mechanisms is the downregulation of MHC molecules, although conflicting results have been reported, depending on cell type and virus studied [51][52][53][54][55]. While a potential mechanism for downregulation of MHC-I surface expression mediated by the viral protein U21 has been reported [56], for MHC-II the effect and mechanism involved are not clear.…”
Section: Isolation Of Mhc-ii Complexesmentioning
confidence: 99%